2006
DOI: 10.1080/17470910601029221
|View full text |Cite
|
Sign up to set email alerts
|

What's domain-specific about theory of mind?

Abstract: Twenty years ago, Baron-Cohen and colleagues argued that autistic performance on false belief tests was explained by a deficit in metarepresentation. Subsequent research moved from the view that the mind has a domain-general capacity for metarepresentation to the view that the mind has a domain-specific mechanism for metarepresentation of mental states per se, i.e., the theory of mind mechanism (ToMM). We argue that 20 years of data collection in lesion patients and children with autism supports a more parsimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 60 publications
1
96
0
4
Order By: Relevance
“…These deficits persist over time and also rapidly worsen in bvFTD patients with marked mPFC atrophy compared to those with limited mPFC atrophy (Kumfor et al, 2014). By contrast, the evidence for ToM impairment in AD has lacked general consensus on whether deficits on ToM tasks are a result of an authentic impairment of ToM (Cosentino et al, 2014;Freedman et al, 2013;Moreau et al, 2016), or due to deteriorating general cognition in the disease, an approach that is compatible with the interactive models of ToM (Dodich et al, 2016;Stone et al, 2006). Few studies in support of a stand-alone ToM deficit in AD have shown that AD patients could fail on basic ToM tasks like gaze-processing (Laisney et al, 2013) and inferring someone's (first-order false) beliefs (Freedman et al, 2013;Le Bouc et al, 2012).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…These deficits persist over time and also rapidly worsen in bvFTD patients with marked mPFC atrophy compared to those with limited mPFC atrophy (Kumfor et al, 2014). By contrast, the evidence for ToM impairment in AD has lacked general consensus on whether deficits on ToM tasks are a result of an authentic impairment of ToM (Cosentino et al, 2014;Freedman et al, 2013;Moreau et al, 2016), or due to deteriorating general cognition in the disease, an approach that is compatible with the interactive models of ToM (Dodich et al, 2016;Stone et al, 2006). Few studies in support of a stand-alone ToM deficit in AD have shown that AD patients could fail on basic ToM tasks like gaze-processing (Laisney et al, 2013) and inferring someone's (first-order false) beliefs (Freedman et al, 2013;Le Bouc et al, 2012).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…A critical appraisal of such inconsistent results for determinants of ToM performance in AD suggests that such differences across studies largely arise due to variations in sample sizes, methodologies, and more importantly the design and complexity of the ToM task administered to the AD population (Bora, Walterfang, & Velakoulis, 2015). arguing that the ability to infer mental states relies on the interaction between lowlevel domain-specific and high-level domain-general mechanisms such as EF (Samson, 2009;Stone & Gerrans, 2006). In that view, efficient complex mental attributions are dependent on a contextual social framework integrating relevant information gathered in the environment by low-level processes (Achim et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the definition of Decety and Jackson [45], who describe this cognitive process as an important part of empathy. Cognitive empathy has also been called internal state empathy [138,182], mentalizing [163], and theory of mind [155]. Empathic accuracy is the accuracy of cognitive empathic inferences [92], and therefore strongly related to cognitive empathy.…”
Section: Cognitive Empathymentioning
confidence: 99%
“…Mentalizing is commonly thought to be a complex social-cognitive process that depends on the development of several precursor mechanisms (Frith and Frith, 1999, Stone andGerrans, 2006).…”
Section: Introductionmentioning
confidence: 99%